2012
DOI: 10.1111/j.1744-7917.2012.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

High temperature determines the ups and downs of small brown planthopper Laodelphax striatellus population

Abstract: Small brown planthopper, Laodelphax striatellus (Fallén) numbers usually drop sharply in the summer and revive quickly in the autumn. However, it is unclear whether and how the high temperature plays a role in this process. The effects of durations of heat exposure (33°C) on life-history traits were examined here. Exposure of adults for 1 day during the oviposition stage led to a very low survival of nymphs. The average longevity of L. striatellus exposed for 1-31 days from oviposition was significantly longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Temperature plays important roles in determining insect survival, development, reproduction and resistance [27,37,38]. Insects exhibit obviously physiological and behavioural responses to thermal stress [15,16,33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Temperature plays important roles in determining insect survival, development, reproduction and resistance [27,37,38]. Insects exhibit obviously physiological and behavioural responses to thermal stress [15,16,33,36].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that temperature plays a more important role than rainfall in the survival and reproduction of SPBH. The optimum temperature for survival and reproduction of SBPH is about 25 °C and higher winter temperatures are apparently favorable for the overwintering of SBPH 54 , as supported by the positive correlation between mean temperature and overwintering SBPH density (Q 0 ) ( Table 6 ). In addition, winter temperature also alters SBPH feeding behavior with warmer winters enhancing feeding activity as indicated by the positive correlation between temperature and viruliferous population density of overwintering SBPH (QV 0 ).…”
Section: Discussionmentioning
confidence: 80%
“…Although previous studies reported the effect of temperature on wing morphs differentiation in the rice planthoppers N. lugens (Zhang, 1983) and L. striatellus (Liu & Zhang, 2012), to date there are no studies referred to the possible role of endosymbionts on the determination of wing morphs in planthoppers. We consider that this topic is an interesting point to be evaluated in further studies.…”
Section: Discussionmentioning
confidence: 99%